Analysis of the complete mitogenomes of three high economic value tea plants (Tea-oil Camellia) provide insights into evolution and phylogeny relationship - Liang, Heng; Qi, Huasha; Wang, Chunmei; Wang, Yidan; Liu, Moyang; Chen, Jiali; Sun, Xiuxiu; Xia, Tengfei; Feng, Shiling; Chen, Cheng; Zheng, Daojun (Frontiers in Plant Science, 2025)
IntroductionTea-oil Camellia species play a crucial economic and ecological role worldwide, yet their mitochondrial genomes remain largely unexplored.MethodsIn this study, we assembled and analyzed the complete mitochondrial genomes of Camellia oleifera and C. meiocarpa, revealing multi-branch structures that deviate from the typical circular mitochondrial genome observed in most plants. The assembled mitogenomes span 953,690 bp (C. oleifera) and 923,117 bp (C. meiocarpa), containing 74 and 76 annotated mitochondrial genes, respectively.ResultsComparative genomic analyses indicated that C. oleifera and C. meiocarpa share a closer genetic relationship, whereas C. drupifera is more distantly related. Codon usage analysis revealed that natural selection plays a dominant role in shaping codon bias in these mitochondrial genomes. Additionally, extensive gene transfer events were detected among the three species, highlighting the dynamic nature of mitochondrial genome evolution in Tea-oil Camellia. Phylogenetic reconstruction based on mitochondrial genes exhibited incongruence with chloroplast phylogenies, suggesting potential discordance due to hybridization events, incomplete lineage sorting (ILS), or horizontal gene transfer (HGT). Furthermore, we identified species-specific mitochondrial markers, which provide valuable molecular tools for distinguishing Tea-oil Camellia species.DiscussionOur findings enhance the understanding of mitochondrial genome evolution and genetic diversity in Tea-oil Camellia, offering essential genomic resources for phylogenetics, species identification, and evolutionary research in woody plants.